TOP no#1 super intensif UN SMP/ MTs 2016 / Muhammad Amien...[et.al]; penyunting, Tin Zulaeha, M. Lukman Hakiem, Rini Yuliana - Muhammad Amien; Tin Zulaeha; Lukman Hakiem, M.; Rini Yuliana (Bisa! Publishing, 2015)
592 hlm. : ilus. ; 26 cm. + CD